Water Properties of Soft Contact Lenses: A Comparative Near-Infrared Study of Two Hydrogel Materials - Jelena Munćan (International Journal of Polymer Science, 2016)
The functionality of soft contact lenses depends strongly on the water content and their water-transport ability. This study was conducted in order to examine the state of water in two sets of soft contact lenses: VSO38, pHEMA Filcon I 1, and VSO50, copolymer of HEMA and VP Filcon II 1 (HEMA = 2-hydroxy-ethyl methacrylate; VP = vinyl pyrrolidone). Hydrogel lenses were studied using near-infrared spectroscopy and the novel Aquaphotomics approach in order to determine the state of water in materials based on their near-infrared spectra. Aquaphotomics approach investigates absorption at specific vibrational bands of water’s covalent and hydrogen bonds which can provide information on how the water structure changes with the structural change of the polymer network. Principal component analysis and specific star-chart “aquagram” were used to analyse water spectral pattern in hydrogel materials. The findings show that material VSO38 has water predominantly organized in bound state, while material with higher water content, VSO50, has more free and weakly hydrogen bonded water. Our findings define in detail exact water species existing and interacting with the polymer network. The results show qualitative and quantitative possibilities of Aquaphotomics for better modelling and understanding water behaviour in hydrogel materials.